Multi-assessment of critical steno-occlusive middle cerebral arteries: transcranial Doppler combined with magnetic resonance angiography. Issue 10 (October 2022) - Mo, Xiuyun; Ma, Zelan; Lin, Hao; Ou, Aihua; He, Xumin; Liu, Guoqing; Zhou, Ting; Zhong, Jingxin
Abstract: Background: Accurate assessment of a stenotic or occluded middle cerebral artery (MCA) is essential before making optimal therapeutic decisions. However, complete occlusion is not always easy to determine for both magnetic resonance angiography (MRA) and neurologists. We aimed to study noninvasive technology using transcranial Doppler (TCD) combined with MRA to assess severe stenosis and occlusion of the MCA. Methods: We studied consecutive patients with severe steno-occlusive MCA by digital subtraction angiography from Oct. 2011 to Mar. 2020 in our stroke center. Hemodynamic measurements of TCD, including peak velocity (PSV), mean flow velocity (MFV) and pulse index (PI), were recorded specifically at the steno-occlusive site by MRA. Results: A total of 152 MCAs of 148 patients were enrolled (60.0 ± 11.5 y, 107 male), including 82 severe stenotic MCAs and 70 occluded MCAs (Group S & Group O) by DSA. There were 86/152 (57%) MCAs showing discontinuity in MRA, which was significantly distributed more in Group O than in Group S (84% vs. 33%, P < 0.001). The PSV and MFV in Group S were greater (264 ± 78 cm/s vs. 33 ± 34 cm/s and 182 ± 61 cm/s vs. 21 ± 23 cm/s, respectively, P < 0.001), while the PI in Group O was greater (0.98 ± 0.49 vs. 0.72 ± 0.17, P < 0.001). PSV was positively correlated with severe MCA stenosis (β = 0.036, P < 0.001, OR = 0.965, 95% confidence interval (CI): 0.952–0.978). In severe steno-occlusive MCA, using PSV and MFV to detect MCA severe stenosis yielded areas under the curve of 0.983 (CI: 0.964–1.0) and 0.982 (CI: 0.962–1.0), respectively. The cutoff points of PSV ≥ 77 cm/s and MFV ≥ 51 cm/s both yielded an optimized sensitivity of 96.3% and specificity of 98.6%. Conclusion: The critical velocity at the steno-occlusive site is reliable for distinguishing between severe MCA stenosis and occlusion. Abstract : Transcranial Doppler; Middle cerebral artery; Intracranial stenosis; Ischemic stroke.